Intravascular endothelioma (endothelioma in situ, systemic endotheliomatosis). Issue 6 (November 1964) - Haber, H.; Harris-Jones, J. N.; Wells, A. L.
Abstract : A woman aged 48 years was found to be suffering from intravascular endothelioma. The initial clinical presentation was the presence of red, painless swellings in the skin of the lower limbs. The other clinical features, and the histological changes in skin biopsies, are described and compared with those in the two previously reported patients. It is suggested that the condition is analogous to the pre-invasive carcinomatous states.